2007
DOI: 10.1007/s00213-007-0806-z
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter occupancy of high-dose selective serotonin reuptake inhibitors during major depressive disorder measured with [11C]DASB positron emission tomography

Abstract: Significantly greater 5-HTT blockade at high dose provides a rationale for raising the dose from the minimum therapeutic dose in specific clinical circumstances. It is likely that 15% unoccupied 5-HTT remains, which should be addressed in future drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 28 publications
4
43
0
Order By: Relevance
“…Imaging techniques such as positron emission tomography (PET) and single-photon emissioncomputed tomography (SPECT) allow in vivo labeling of SERT in the brain, which can be used to study their occupancy. Till date, several imaging studies measured SERT occupancy after short or prolonged treatment with SSRIs (Klein et al, 2006(Klein et al, , 2007Voineskos et al, 2007;Parsey et al, 2006;Takano et al, 2006;Catafau et al, 2006;Herold et al, 2006;Cavanagh et al, 2006;Erlandsson et al, 2005;Suhara et al, 2003;Kent et al, 2002;Meyer et al, 2001bMeyer et al, , 2004Hiltunen et al, 1998). Particularly, Meyer et al (2004) showed 60-80% SERT occupancy after standard clinical doses of SSRIs, and demonstrated curvilinear doseresponse relationships for SERT occupancy by SSRIs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging techniques such as positron emission tomography (PET) and single-photon emissioncomputed tomography (SPECT) allow in vivo labeling of SERT in the brain, which can be used to study their occupancy. Till date, several imaging studies measured SERT occupancy after short or prolonged treatment with SSRIs (Klein et al, 2006(Klein et al, , 2007Voineskos et al, 2007;Parsey et al, 2006;Takano et al, 2006;Catafau et al, 2006;Herold et al, 2006;Cavanagh et al, 2006;Erlandsson et al, 2005;Suhara et al, 2003;Kent et al, 2002;Meyer et al, 2001bMeyer et al, , 2004Hiltunen et al, 1998). Particularly, Meyer et al (2004) showed 60-80% SERT occupancy after standard clinical doses of SSRIs, and demonstrated curvilinear doseresponse relationships for SERT occupancy by SSRIs.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, Meyer et al (2004) showed 60-80% SERT occupancy after standard clinical doses of SSRIs, and demonstrated curvilinear doseresponse relationships for SERT occupancy by SSRIs. However, high doses of SSRIs were rarely studied (Voineskos et al, 2007), and dose escalation was never studied.…”
Section: Introductionmentioning
confidence: 99%
“…In our view, PET studies with the radioligands that are currently available for assessing serotonergic functions in the living human brain have failed to provide conclusive evidence for aberrant serotonergic mechanisms in depressive disorders. We have noted, however, that receptor occupancy of serotonin transporters can be assessed reliably by PET with [ 11 C]DASB or [ 11 C]McNeil 5652 (Voineskos et al 2007;. Perhaps studies of receptor occupancy before and during antidepressant therapies can provide a means of determining whether treatment-resistance stems from inadequate receptor blockade.…”
Section: Recent Pet Studies Of Serotonin In Depressive Disordersmentioning
confidence: 99%
“…This is based on studies reporting lower plasma availability of the serotonin (5-HT) precursor tryptophan for uptake into the brain, reduced cerebrospinal fluid concentration of the 5-HT metabolite 5-hydroxyindoleacetic (5-HIAA) and decreased platelet 5-HT uptake in depressed patients, suggesting diminished brain 5-HT uptake and metabolism (Maes and Meltzer 1995;Neumeister et al 2004). The level of 5-HT in the synaptic cleft is mainly regulated by the 5-HT transporter (5-HTT), which is targeted by most antidepressants (Meyer et al 2004;Suhara et al 2003;Voineskos et al 2007). Interestingly, the human 5-HTT gene, located on chromosome 17q11.1-q12 (Lesch et al 1994), contains a 5-HTT-linked polymorphic region (5-HTTLPR) with two functional variants: the short (s) form and the long (l) form (Greenberg et al 1999;.…”
Section: Introductionmentioning
confidence: 99%